Sensorimotor versus core stabilization home exercise programs following total knee arthroplasty: a randomized controlled trial - Gülek Karadüz, Ebru; Demirbaş, Rıza Emrah; Ya?cıo?lu, Ayça; Badıllı Hantal, Şule (My University, 2024)
Introduction: Although total knee arthroplasty (TKA) is a frequently-performed surgery, no standard rehabilitation approach has yet been established. The study aimed to compare the effects of sensorimotor and core stabilization exercises on proprioception, range of motion, balance, and function following TKA. Material and methods: This randomized trial was conducted with 40 female patients (69.38 ± 5.81 years) who had undergone unilateral TKA. The participants were randomly allocated to either a sensorimotor group (N = 20) or a core stabilization group (N = 20). The patients performed exercise programs over a six-week period between the second and eighth weeks postoperatively. Proprioception, knee and hip range of motion, Knee Injury and Osteoarthritis Outcome Scale (KOOS), Berg Balance Scale, Timed Up and Go test, and 5-times sit-to-stand test were measured on three separate occasions: preoperative (E0), before treatment (E1), and after treatment (E2) during postoperative rehabilitation. Results: Both groups demonstrated statistically significant improvements for all outcomes between E1 and E2 (p < 0.05). However, the sensorimotor group exhibited a significantly improvement compared to the stabilisation group regarding KOOS-sportive recreational activities (p < 0.001). Additionally, both treatment programs provided recovery of knee and hip ROM and proprioception (p < 0.05). Conclusions: Core stabilization exercises are effective for improving balance, proprioception, function, and ROM; however, sensorimotor exercises are more effective in the acquisition of sports and recreational activities. Both programs provide effective rehabilitation on a bilateral extremity.
Keywords: Arthroplasty; Functional Performance; Knee; Rehabilitation; Replacement